Successful treatment of plasma exchange for rapidly progressive interstitial lung disease with anti-MDA5 antibody-positive dermatomyositis: A case report. Issue 15 (April 2018) - Endo, Yushiro; Koga, Tomohiro; Suzuki, Takahisa; Hara, Kazusato; Ishida, Midori; Fujita, Yuya; Tsuji, Sosuke; Takatani, Ayuko; Shimizu, Toshimasa; Sumiyoshi, Remi; Igawa, Takashi; Umeda, Masataka; et al.
Abstract: Rationale: As the initial treatment of rapidly progressive interstitial lung disease (RPILD) with antimelanoma differentiation-associated gene 5 antibody (anti-MDA5 Ab)-positive dermatomyositis (DM) patients, a combination of corticosteroids, cyclophosphamide, and calcineurin inhibitor is recommended. However, some of these patients have poor prognoses despite such intensive treatment. Other more effective treatments are desired. We report the case of an anti-MDA5 Ab-positive DM patient who had developed RPILD despite intensive treatments; she was treated successfully by a short-term plasma exchange (PE). Patient concerns: A 71-year-old Japanese woman was admitted to the rheumatology department of another hospital with progressive muscle weakness of the limbs and erythema on both upper eyelids and the fingers of both hands. She was suspected of having classical DM (CDM) based on the findings of typical skin and myositis. Although a chest computed tomography (CT) examination showed no findings of interstitial pneumonia at the first visit to the department, she newly presented interstitial pneumonia during her admission and her anti-MDA5 Ab titer was elevated. Diagnoses: She was diagnosed with interstitial lung disease (ILD) with anti-MDA5 Ab-positive DM. Interventions: She was treated with 1000 mg of methyl-prednisolone pulse, 500 mg of intravenous cyclophosphamide therapy (IVCY) followed by prednisolone 40 mg/day with tapering, and oral cyclosporine 200 mg/day. However, her interstitial pneumonia worsened with increasing breathing difficulty and an increasing serum ferritin level. She was transferred to our department, and we initiated PE as an additional treatment. Outcomes: After the PE treatment, all laboratory findings, for example, ferritin, KL-6, and the titer of anti-MDA5 Ab showed marked improvement, and the patient's skin symptoms and active interstitial pneumonia were relieved. Lessons: Our patient's case suggests that PE may be effective for RPILD in anti-MDA5 Ab-positive DM patients.